Virulensi Virus Newcastle Disease Isolat Lapang Berdasarkan Analisis Bioinformatika Gen Protein Hemaglutinin - Neuraminidase - Fedry Rell; Anak Agung Mirah Adi; I Gusti Ngurah Kade Mahardika (Udayana University, 2015)
Newcastle disease virus (NDV) is very contagious disease agent, and causes many outbreaks trough out thecountry of Indonesia. This study was conducted to determine the virulence of Bali field isolate of NDVbased on haemaglutinin-neuraminidase (HN) protein genes. Four field isolates from different locationswere propagated at fertilized chicken eggs of 9 days old. Allantoic fluid was harvested and NDV wasconfirmed using standard haemaglutination (HA) and haemaglutination inhibition test (HI) methods. Thefragment of HN protein gene was amplified using RT-PCR. The product was sequenced using Big-Dyetermination method. All four isolates grew well with the titer of 2[5]-2[9] HA unit and could be confirmedusing HI test. The HN genes, however, exhibited variations at its 3-D structure and hydrophobicity betweenthe virus that previously circulated in Indonesia and vaccine virus. It is concluded that all four Bali’sisolates under this study are virulent VND of the genotype VII. Further testing is needed to justify the bestformula of NDV vaccine to be used trough out Indonesia.